Team-based learning (TBL) in clinical disciplines for undergraduate medical students—a scoping review - Sterpu, Irene; Herling, Lotta; Nordquist, Jonas; Rotgans, Jerome; Acharya, Ganesh (BMC medical education, 2024)
Background Team-based learning (TBL) is an evidence-based pedagogical method that has been used in undergraduate medical education since 2001. However, its use in clinical disciplines is rarely reported, and the impact of its implementation is not known. The aim of this study was to explore and map the published literature on the impact of implementing TBL in clinical disciplines in undergraduate medical education. Methods A comprehensive search of Medline, Education Resources Information Center (ERIC), and Web of Science databases was performed on November 24, 2021 and updated April 6, 2023, using relevant Medical Subject Headings (MeSH) and free-text terms. Original research studies reporting on the implementation of TBL in clinical disciplines in undergraduate medical education published in peer-reviewed English language journals were included irrespective of their methodological design. Results The initial search identified 2,383 records. Of these, 49 met the inclusion criteria. Most of the studies ( n = 44, 90%) described the implementation of a modified version of TBL in which one or more TBL steps were missing, and one study had undefined protocol for the implementation. The most reported outcomes were knowledge acquisition ( n = 38, 78%) and students’ satisfaction or attitudes toward TBL ( n = 34, 69%). Despite some differences in their results, the studies found that implementing TBL is associated with increased knowledge acquisition ( n = 19, 39%), student engagement ( n = 6, 12%), and student satisfaction ( n = 31, 63%). Conclusions Most of the studies reported positive results in students’ satisfaction and students’ engagement, whilst the results on knowledge acquisition and retention were more contradictory. In most of the studies, TBL was implemented in a modified form and diverse comparators were used. The methodological quality also varied. Thus, no unequivocal conclusions could be drawn regarding the value of implementing TBL in clinical disciplines. More studies with rigorous methodologies are needed in this field.